Employability and Human Resource Management Tools - Fatma Chikhaoui (Journal of Business and Management Review, 2022)
In the current context, the notion of employability is a huge hit in several research projects. Employability is a concept mobilized in different scientific fields and especially in the human resource management and specifically by practitioners to develop the employability of employees. We understand the growing emphasis on this concept as a result of the change of the psychological contract and the divorce between loyalty and job security. The employee-employment relationship is no longer the same. Accordingly, a new working relationship is being established from an employability-development perspective where employers and employees are embarked together in a win-win pact under the banner of employability development. The aim of this research is to provide a review of the literature about the concept of employability and highlights human resource management tools susceptible to its development